A telemetric system for the analysis of six muscle activities in swimming - Rouard, A. H.; Quezel-Ambrunaz, G.; Billat, R. P. (Swimming Science V, 1988)
In competitive swimmin~ oxygen uptake, drag, and lift all increase with swimming speed. These modifications can produce and/or result from changes in muscular activity. Thus, one might wonder whether muscular contractions and synchronizations also increase in relation to an increase of swimming speed. In order to answer the above questions, equipment for electromyography measurements was required. There was no standard apparatus for this kind of measurement on the market, and a review of electronics journals such as the Institute of Electronical Electrical Engineers (IEEE) and of publications on electromyography in sports showed that telemetric systems have not been widely used and often limited to a few channels (Oarys & Olbrecht, 1982; Lewillie, 1974; Piette & Oarys, 1979). So, the first step was to conceive and refine a specific apparatus. To accomplish this, researchers, engineers, technicians, and trainers decided three criteria: • Object of study: Our goal was to collect simultaneously the electrical activities of six muscles that could be visualized directly by the subject utilizing a display system. • Subject disturbance: The system should not be too cumbersome or too difficult to attach. It should also be light. • Water-proofing: The apparatus must be waterproof, unbreakable, and reliable.